2020
DOI: 10.1016/j.heliyon.2020.e03625
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay-guided isolation and identification of antidiabetic compounds from Garcinia cowa leaf extract

Abstract: Garcinia cowa Roxb. ex Choisy (Clusiaceae) is a Thai local edible plant, which has been used for the treatment of diabetes. The aim of this study is to discover and identify bioactive compounds related to antidiabetic properties from the leaf extract of G. cowa. α-Glucosidase inhibitory bioassay-guided isolation of the ethyl acetate extract of the leaves of G.cowa resulted in the isolation and identification of 11 compounds. Of these, a decahydro-1Hxanthene derivative, garciniacowone K (1), was identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 38 publications
0
30
0
1
Order By: Relevance
“…A colorimetric α -glucosidase assay was carried out by the previously described procedure [ 18 ]. Briefly, the sample solution was dissolved in DMSO after the solutions were diluted with a phosphate buffer (100 mM KH 2 PO 4 , pH 6.9) become DMSO (10%, v/v ) concentration.…”
Section: Methodsmentioning
confidence: 99%
“…A colorimetric α -glucosidase assay was carried out by the previously described procedure [ 18 ]. Briefly, the sample solution was dissolved in DMSO after the solutions were diluted with a phosphate buffer (100 mM KH 2 PO 4 , pH 6.9) become DMSO (10%, v/v ) concentration.…”
Section: Methodsmentioning
confidence: 99%
“…The information on instruments and materials was the same as previous reports ( Raksat et al., 2019 ; Phukhatmuen et al., 2020 ; Suthiphasilp et al., 2020 ). For more details, please see Supplementary Material.…”
Section: Methodsmentioning
confidence: 99%
“…A colorimetric α -glucosidase assay was conducted according to the previously described method ( Sharma et al., 2019 ; Phukhatmuen et al., 2020 ; Suthiphasilp et al., 2020 ), using acarbose as a positive control (IC 50 = 83.5 μM).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from cytotoxic activity, the results of previous studies also showed that asam kandis (Garcinia cowa Roxb.) has antidiabetic 5 , antioxidant, antimutagenic 6 , antibacterial 7,8,9 and anti-inflammatory activities 10 . It is hoped that the explanation from this review can increase knowledge and can contribute to the development of anticancer drugs from natural ingredients.…”
Section: Introductionmentioning
confidence: 99%